TINJAUAN YURIDIS PARTISIPASI MANTAN NARAPIDANA SEBAGAI PESERTA CALON KEPALA DAERAH - Josviranto, Micael (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The participation of ex-convicts in the nominating bourse legally has been regulated in statutory regulations from philosophical foundations, constitutional foundations and other relevant regulations. So, there is no castration of a person's rights but further stipulated in the Act so that it continues to participate politically for the country.